Influence of Optical Thickness and Inclination Angle on Coupled Natural Convection and Thermal Radiation in Inclined Cavities - Ghaziani, Khadijeh; Cornelio, Omar Mar (Mechanical Technology and Engineering Insights, 2024)
In this study, the effect of thermal radiation on heat transfer via natural convection in inclined cavities under inclination angles of 45° and 60° is studied numerically. For modeling the flow field and heat transfer, the conservation laws of mass, momentum, and energy are solved using the Finite Volume Method (FVM). In contrast, the SIMPLE algorithm is employed to solve the pressure-velocity coupling. The buoyancy force resulting from the temperature gradient is considered using the Boussinesq approximation. In the first step, the characteristics of natural convection heat transfer in inclined cavities are studied in the absence of radiation. Then, the effect of thermal radiation is studied for radiative participation and non-participation of the fluid medium. To assess the accuracy of numerical solutions, results such as streamlines, isotherms, and Nusselt number profiles are compared with those reported in the literature and found to be in close agreement. The results show that the optical thickness has a considerable effect on the flow field, the strength of recirculation, the temperature profile, and, ultimately, the heat transfer performance. In other words, the importance of radiation heat transfer increases with increasing optical thickness. Consequently, the average Nusselt number decreases as the optical thickness increases. Moreover, an increase in the angle of inclination weakens buoyancy-induced flow, thereby reducing recirculation and heat transfer. The combined influence of geometric inclination and radiation reveals a significant interaction between fluid mechanics and heat transfer, which is crucial to understanding the thermo-fluid dynamics of inclined cavities. The results obtained from the present investigation are expected to provide valuable information for the design of optimal thermal systems in which interactions between convection and radiation play a key role.